PENGARUH PENGALAMAN KERJA, PENILAIAN PRESTASI KERJA DAN HUBUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT. JASARAHARJA PUTERA CABANG PEKANBARU - Muthia Amanta Dwi Putri; Marzolina '; Rovanita Rama (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The study held in PT. Jasaraharja Putera Pekanbaru branch in order to know and analyze the influence of work experience, job achievement assessment and job relation to employee’s performance. Population are all employees, consist of 53 employees that selected by using census method. Variables are work experience, job achievement assessment and job relation as independent and performance as dependent. Data analyzed by using descriptive and multiple linear regression analysis assisted by SPSS 22 for windows. The study reveals that simultaneously, work experience, job achievement assessment and job relation significantly influence employee’s performance. However, only job achievement assessment and job relation have significant effect while work experience has no significant effect to employee’s performance. It is recommended to ideally increase employee’s performance by enhancing the work experience, job achievement assessment process and job relation among personals in organization.Keywords: Work Experience, Job Achievement Assessment, Job Relation and Performance